Farmer-led climate adaptation: Project overview - Chevallier, Romy; Tuyishime, Norbert (2024)
The Eastern Africa Farmers Federation (EAFF) in collaboration with Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), is implementing a project to showcase best practice examples of farmer-led adaptation in managing the negative impacts of climate change on agriculture.